VESICULOBULLOUS LESIONS: A JOURNEY THROUGH HISTOPATHOLOGY IN TERTIARY CARE CENTRE. - Dr. Sheetal Munde, Dr. Pramod Sarwade, Dr. Deelip Jaiswal, Dr. Bharat Sonwane (South Eastern European Journal of Public Health, 2025)
Introduction: Vesiculobullous disorders represent a heterogeneous group of dermatoses with protean manifestations usually associated with fluid filled skin lesions. They usually occur as a part of the spectrum of various infectious, drug-induced, genetic, inflammatory and autoimmune disorders. Distinguishing between different diseases can be challenging, as they may share similar appearances, making clinical diagnosis difﬁcult. Histopathology serves as a crucial tool in resolving diagnostic uncertainties, acting as a bridge towards accurate identification. Aim and Objectives: To establish clinical and histopathological correlation in diagnosing disease. To study definitive diagnosis in diseases with overlapping presentation Material and Method: In the present study evaluation of vesiculobullous lesions were studied over the period of 2 years (July 2022- July 2024). A total number of 58 skin biopsies were received in histopathology section in department of pathology were studied. Results: In Vesiculobullous group of disorders, there were 33(56.8%) cases of Pemphigus Vulgaris,Pemphigus foliaceous 12 (20.6%),Bullous pemphigoid 11(18.9%),Darriers disease1 (1.72%),pemphogoid Gestationis 1 (1.72%).there was female preponderance, age group affected was in range of 25 to 65 years. Conclusion: Correct diagnosis plays an important role in treatment and counselling about type, duration and prognosis of disease, maintaining remission and avoidance of aggravating or causative factors.